Diagnosis, Prevention and Treatment of Aspirin-Induced Asthma and Rhinitis - Bochenek, G.; Banska, K.; Szabo, Z.; Nizankowska, E.; Szczeklik, A. (Current Drug Targets - Inflammation & Allergy, 2002)
Bronchial asthma is not a homogenous disease. Several variants of asthma can be distinguished. One of them is aspirin-induced asthma. In this distinct clinical syndrome, aspirin and most other nonsteroidal anti-inflammatory drugs that inhibit cyclooxygenase-1 precipitate rhinitis and asthma attacks. This type of asthma affects 5-10% of adult asthmatics, but remains largely underdiagnosed. The natural history of aspirin-induced asthma (AIA) has been described, based on an extensive pan-European survey. Aspirin provocation tests with improved diagnostic accuracy have been developed, although no in-vitro tests has been found to be of diagnostic value. Recent interest in AIA has been stirred by the finding of alterations in arachidonate metabolic pathways, leading to cysteinyl-leukotriene overproduction. LTC4 synthase is overexpressed in bronchi and its mRNA is upregulated in peripheral blood eosinophils. The gene coding for LTC4 synthase exists in two common alleles, one of which appears to be associated with a severe, steroid-dependent type of asthma. New highly specific COX-2 inhibitors appear to be a safe alternative for patients with aspirin-induced asthma.
Keywords: Aspirin-Induced Asthma